Kinetics of Oxidation of Some Dihydroxy Ethers by Permanganate in Perchloric Acid Medium - Pal, Biswajit; Nath Basu, Samarendra; Kali Sen Gupta, Kalyan (Asian Journal of Chemistry, 2010)
Reactivities of some dihydroxy ethers, viz., diethylene glycol, triethylene glycol, tetraethylene glycol, polyethylene glycol (200, 400, 600 LR) by permanganate have been studied in presence of perchloric acid. The reaction rate increases with increase in [H+] and the order with repect to [H+] is 0.4 ±0.1 at [H+] ≤0.4 mol dm-3 but 1.3 ± 0.1 at [H+] > 0.4 mol dm -3. The reaction occurs through the protonation of ether group of the substrate in a fast preequilibrium followed by a slow rate-determining oxidation step. The substrates are oxidised to give formaldehyde. The reactions have been shown to occur by one-step two-electron transfer process.